Profil Kepercayaan Diri Siswa Kelas X DKV SMKS Krija Bhakti Utama - Fitriani, Irma (Ma'soem University, 2025)
The background of this research is caused by the low self-confidence felt by students can be triggered due to social pressure and high expectations, both from peers and the family environment. This research aims to look at the profile of self-confidence in class X DKV SMKS Krija Bhakti Utama for the 2023/2024 academic year. The research method used in this research is a descriptive quantitative method. Data was collected by distributing instruments to 93 students in class X DKV Kija Bahkati Utama SMKS. The results show that the self-confidence profile in class 91.4% of students have a medium level of self-confidence and 7.5% of students have a high level of self-confidence. From the results of this research, an action plan program was created, which allows increasing self-confidence in the research location, and also as a product of the research results.